Comparing taxes as a percentage of sugar-sweetened beverage prices in Latin America and the Caribbean - Maxime Roche; Miriam Alvarado; Rosa Carolina Sandoval; Fabio da Silva Gomes; Guillermo Paraje (Elsevier, 2022)
Summary: Background: Excise taxes can be used to reduce the consumption of sugar-sweetened beverages (SSBs), an important preventable risk factor for noncommunicable diseases. This study aimed to compare novel standardized indicators of the level of taxes applied on SSBs as a percentage of the price across beverage categories in Latin America and the Caribbean. Methods: We used a method developed by the Pan American Health Organization and adapted from the World Health Organization's tobacco tax share. The analysis focused on the most sold brand of five categories of non-alcoholic beverages. Data were collected by surveying ministries of finance and reviewing tax legislation in effect as of March 2019. Findings: Of the 27 countries analyzed, 17 applied excise taxes on SSBs. Of these, median excise taxes represented the highest share of the price for large sugar-sweetened carbonated drinks (6·5%) and the lowest for energy drinks (2·3%). In countries where excise taxes were applied on bottled waters, tax incidence exceeded the one applied on most SSBs. Overall, excise tax shares were higher in Latin America than in the Caribbean. Including all other indirect taxes (e.g., value added tax), median total tax shares were between 12·8% and 17·5%. At least two countries earmarked part of SSB excise tax revenues for health purposes. Interpretation: Excise tax levels are generally low in the region. From a public health perspective, tax rates could be increased, and tax designs improved (e.g., excluding bottled waters). The method describe here provides a feasible and informative way to monitor SSB taxation and could be replicated in other regions and over time. Funding: Bloomberg Philanthropies through the Global Health Advocacy Incubator.